Lipoprotein Associated Coagulation Inhibitor, Factor VII, Antithrombin III, and Monocyte Tissue Factor Following Surgery - Carson, Steven D; Haire, William D; Broze, George J, Jr.; Novotny, William F; Pirrucello, Samuel J; Duggan, Michael J (Thrombosis and Haemostasis, 1991)
Fifteen patients undergoing major surgical procedures were evaluated for lipoprotein associated coagulation inhibitor (LACI) antigen, factor VII (F VII), antithrombin III (AT III), and peripheral blood monocyte tissue factor (TF) activity immediately before surgery and on following days. A peak in monocyte TF activity occurred between the first and fifth days after surgery in 10 of the patients, while LACI, F VII, and AT III levels dropped in a qualitatively parallel manner in 8 of these patients. LACI, F VII, and AT III levels decreased after surgery in two additional patients even though TF activity also decreased after surgery in these patients. In the remaining 3 patients who developed infections during the study, TF activity rose within 2 days of the diagnosis of infection in addition to the postoperative peak. In two of these patients, LACI levels increased dramatically near the end of the study period without concomitant changes in F VII and AT III. Overall, the presurgical TF levels in disrupted monocytes varied 52-fold and the maximal TF activity varied 24-fold among patients. The TF response following surgery is therefore heterogenous in both temporal occurrence and magnitude of the postsurgical peak. The patients also varied considerably in the presurgical levels of monocyte TF activity. A possible association between the level of presurgical TF activity and the magnitude of the postsurgical peak was noted. Thirteen of the patients had malignant disease, and, as a group, had presurgical levels of LACI (83 ± 26; mean ± SD), F VII (124 ± 22) and AT III (111 ± 14) within the normal ranges established with pooled reference plasma and similar values for three normal donors studied over the same period (AT III 121 ± 6, LACI 95 ± 4, and F VII 112 ± 29). No cause-effect relationship could be established between changes in TF activity and changes in the other factors measured. Patient- or therapy-specific variables may determine postoperative variations in LACI, F VII, AT III, and monocyte TF.